Corrosion Resistance of Ti6Al4V Titanium Alloy with Modified Surfaces - Skublova, Lenka; Skorik, Viktor; Mrazikova, Rastislava; Hadzima, Branislav (Communications - Scientific Letters of the University of Zilina, 2010)
Corrosion behaviour of biocompatible Ti6Al4V titanium alloy has been investigated by using electrochemical impedance spectroscopy in Hank's physiological solution for two modified states of titanium surface. On the basic of type and shape of Nyquist curves obtained from EIS measurements probable mechanisms of corrosion in a specific corrosion system are assigned.
Keywords: no keywords